Dairy sector: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
In the majority of ACP countries, local production of dairy products falls short of the growing domestic demand. As a way to cope with this situation, expanding local production is just one policy option, the alternative being the use of imported milk and milk powder for the development of local processing industries. This Executive Brief analyses the 2012-13 developments of the dairy sector at global level, in the EU and in each ACP sub-region. Special attention is given to the implications of the progressive abolition of the EU milk quota, which is likely to lead to increased milk production and subsequently to increased exports (mainly of milk powder). The Brief also highlights some of the challenges for ACP producers to respond to the rising demand for dairy products, in terms of strategies for consolidating regional markets and balancing imports and local milk production.